La peste – maladie ou activité démoniaque ? Les récits des pestes dans les Histoires admirables de Benoît Gonon - Trębska, Marta Elżbieta (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In his Histoires admirables (Lyon, 1653), Benoît Gonon, a little-known author of shortexemplary novels, tells many stories about horrific cases of pestilence sweeping and tormentingpeople in various parts of the world throughout the ages – from late Antiquity to morerecent plague of the XIVth century which took Europe by storm. Gonon sees those gruesomestories as an excellent opportunity to teach his readers an important lesson and ask whethersuch an event could possibly be, rather than a natural phenomenon, an ultimate punishmentsent by the wrath of God. One of the sins that could demand such a punishment is idolatry,considered by Gonon himself, to be the most reprehensible of all the sins. It is merely surprisingthen, that in his stories, the pestilence is being depicted as a demon – or an idol. In thispaper, I am going to explore the stories about pestilence in Histoires admirables and answer thequestions about the nature of pestilence. Which crimes could lead to people being punished insuch a way? How to appease God’s wrath? Can pestilence manifest itself by demonic activity?